2022
DOI: 10.47197/retos.v42i0.88098
|View full text |Cite
|
Sign up to set email alerts
|

Repercusión en la calidad de vida, salud y práctica de actividad física del confinamiento por Covid-19 en España (Effects on quality of life, health and practice of physical activity of Covid-19 confinement in Spain)

Abstract: En España, la declaración del estado de alarma por la pandemia Covid-19, supuso que entre el 14 de marzo y el 2 de mayo de 2020, 47 millones de habitantes estuvieran confinados y sólo pudieran salir a cubrir necesidades básicas. Ante este hecho es oportuno analizar su impacto sobre la salud, tomando en consideración cómo afectó a la práctica de la actividad física. Se administró un cuestionario ad hoc. Los participantes fueron 1046 personas (hombre 48.57% y mujer 51.43%) y con una edad media de 40 (± DT 13.35 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
10

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 19 publications
1
9
0
10
Order By: Relevance
“…The pandemic has unequivocally altered the lifestyles of the different groups that make up the university community (students, faculty and administrative and service personnel), as has been pointed out in other studies (Fornili et el., 2021; Odriozola-González, Planchuelo-Gómez, Irurtia & de Luis-García, 2020). These facts have been confirmed both by studies whose sample was the general population (Balanzá-Martinez et al, 2021;García-Tascón et al, 2021;Khan, Sultana, Hossain, Hasan, Ahmed & Sikder, 2020;Magaz-González et al, 2021;Xiong et al, 2020;), or health professionals (Dosil Santamaría, Ozamiz-Etxebarria, Redondo Rodríguez, Jaureguizar Alboniga-Mayor & Picaza Gorrotxategi, 2020;Serrano-Ripoll et al, 2020), and also by those focussing only on university students (Imaz-Aramburu et al, 2021;Khan, Sultana, Hossain, Hasan, Ahmed & Sikder 2020;Romero-Blanco, Rodríguez-Almagro, Onieva-Zafra, Parra-Fernández, Prado-Laguna & Hernández-Martínez, 2020;Giuntella, Hyde, Saccardo & Sadoff, 2021;Savage et al, 2020;Ruiz-Zaldivar et al, 2021;Yun et al, 2021;Wang & Zhao H 2020;Saravanan, Mahmoud, Elshami & Taha 2020;Kaparounaki, Patsali, Mousa, Papadopoulou, Papadopoulou, & Fountoulakis 2020;Bánhidi & Lacza 2020). Therefore, although the current study did not specifically analyse the possible effects on the sample of stress, anxiety or depression, there are certain responses that could be related to these: almost 90% are quite or very concerned about the COVID-19 pandemic, 75.2% think that it has affected them negatively, one fifth think that the worst is yet to come, and two thirds consider that there is a medium to high probability of being infected by COVID-19.…”
Section: Impact Of Covid-19mentioning
confidence: 63%
See 1 more Smart Citation
“…The pandemic has unequivocally altered the lifestyles of the different groups that make up the university community (students, faculty and administrative and service personnel), as has been pointed out in other studies (Fornili et el., 2021; Odriozola-González, Planchuelo-Gómez, Irurtia & de Luis-García, 2020). These facts have been confirmed both by studies whose sample was the general population (Balanzá-Martinez et al, 2021;García-Tascón et al, 2021;Khan, Sultana, Hossain, Hasan, Ahmed & Sikder, 2020;Magaz-González et al, 2021;Xiong et al, 2020;), or health professionals (Dosil Santamaría, Ozamiz-Etxebarria, Redondo Rodríguez, Jaureguizar Alboniga-Mayor & Picaza Gorrotxategi, 2020;Serrano-Ripoll et al, 2020), and also by those focussing only on university students (Imaz-Aramburu et al, 2021;Khan, Sultana, Hossain, Hasan, Ahmed & Sikder 2020;Romero-Blanco, Rodríguez-Almagro, Onieva-Zafra, Parra-Fernández, Prado-Laguna & Hernández-Martínez, 2020;Giuntella, Hyde, Saccardo & Sadoff, 2021;Savage et al, 2020;Ruiz-Zaldivar et al, 2021;Yun et al, 2021;Wang & Zhao H 2020;Saravanan, Mahmoud, Elshami & Taha 2020;Kaparounaki, Patsali, Mousa, Papadopoulou, Papadopoulou, & Fountoulakis 2020;Bánhidi & Lacza 2020). Therefore, although the current study did not specifically analyse the possible effects on the sample of stress, anxiety or depression, there are certain responses that could be related to these: almost 90% are quite or very concerned about the COVID-19 pandemic, 75.2% think that it has affected them negatively, one fifth think that the worst is yet to come, and two thirds consider that there is a medium to high probability of being infected by COVID-19.…”
Section: Impact Of Covid-19mentioning
confidence: 63%
“…However, Giuntella, Hyde, Saccardo, & Sadoff (2021), in their longitudinal study, found large alterations to physical activity, sleep, time use and mental health (steps taken per day reduced by more than a half, an increase from 25 to 30 minutes of sleep time per night, a decrease in social relationships by more than a half to less than 30 minutes a day, and an increase to over 5 hours daily spent in front of a screen, while simultaneously rates of depression also increased). Similarly, García-Tascón et al (2021) showed that Spanish people who did no physical activity at all, increased during lockdown, or Alarcón Meza & Hall-López ( 2021) that indicate that Mexican university athletes reduced their level of exercise during lockdown. Furthermore, Zamarripa, Marroquin-Zepeda, Ceballos-Gurrola, Flores-Allende & Garcia-Gallegos (2021) reported that Mexican adults increased sedentary behaviors such as watching TV/play video games, listen to music... while the level of physical activity tended to decrease and Savage et al, (2020) found that physical activity among British university students decreased during the lockdown.…”
Section: Impact Of Covid-19mentioning
confidence: 98%
“…Los beneficios que pueden ofrecer intervenciones de danza y prácticas expresivas para personas con enfermedades como la EM, se ven comprometidos en un escenario como el que se vive de pandemia por la COVID-19, donde preservar de un posible contagio puede significar dejar de participar en programas presenciales de este tipo u otros. Si bien la actividad física parece ser en general beneficiosa para reducir las consecuencias mentales y físicas en confinamiento (Camacho-Cardenosa, et al, 2020), en todas las esferas de nuestra sociedad, la pandemia ha afectado a las condiciones de práctica de actividad física, tanto en la disminución de cantidad e intensidad como en las disciplinas practicadas (García-Tascón, et al, 2021). Como medio para mitigar ciertos efectos psicológicos producidos por la pandemia (frustración, aislamiento, estrés, miedo), cobra importancia la actividad física en el hogar como fenómeno, con la expansión de prácticas virtualizadas y el diseño de intervenciones de práctica ad hoc como éste que se presenta.…”
Section: La Dimensión Expresiva Del Movimiento Como Oportunidad De Bienestar Emocionalunclassified
“…Para operacionalizá-la, governantes impuseram múltiplas restrições de acesso à espaços públicos e privados; confinamentos residenciais obrigatórios (lockdown); fechamentos temporários de estabelecimentos comerciais e industriais; usos de máscaras (Adil et al, 2020;Singh et al, 2020). A implantação de tal quadro gerou consequências negativas sobre as atividades econômicas, culturais, educacionais, políticas e sociais que vinham até então acontecendo rotineiramente (Clemente-Suárez et al, 2021;Daher-Nashif, 2021;García-Tascón et al, 2021;Jiménez-Barret & Borges, 2021).…”
Section: Introductionunclassified